Circulating Levels of MicroRNAs Associated With Hypertension: A Cross-Sectional Study in Male and Female South African Participants - Matshazi, Don M.; Weale, Cecil J.; Erasmus, Rajiv T.; Kengne, Andre P.; Davids, Saarah F. G.; Raghubeer, Shanel; Davison, Glenda M.; Matsha, Tandi E. (Frontiers in Genetics, 2021)
MicroRNAs are non-coding, post-transcriptional regulators of gene expression and their dysregulation has been associated with development of various diseases, including hypertension. Consequently, understanding their role in the pathogenesis and progression of disease is essential. Prior research focusing on microRNAs in disease has provided a basis for understanding disease prognosis and offered possible channels for therapeutic interventions. Herein, we aimed to investigate possible differences in the expression profiles of five microRNAs in the blood of participants grouped on the basis of their hypertension status. This was done to elucidate the possible roles played by these microRNAs in the development of hypertension. Using quantitative reverse transcription polymerase chain reaction, we evaluated the expression levels of miR-126-3p, 30a-5p, 182-5p, 30e-3p and 1299 in the whole blood of 1456 participants, normotensive (n=573), screen-detected hypertensive (n=304) and known hypertensive (n=579). The expression of miR-126-3p and 182-5p was significantly higher in known hypertensives relative to both screen-detected hypertensives and normotensives, and also in screen-detected hypertensives vs normotensives. A significant association between the expression of miR-126-3p, 182-5p and 30a-5p and known hypertension was also evident. This study demonstrated dysregulated miR-126-3p, 182-5p and 30a-5p expression in hypertension, highlighting the possible efficacy of these microRNAs as targets for the diagnosis of hypertension as well as the development of microRNA-based therapies.